Nasal colonisation by Staphylococcus aureus depends upon clumping factor B binding to the squamous epithelial cell envelope protein loricrin. - Michelle E Mulcahy; Joan A Geoghegan; Ian R Monk; Kate M O'Keeffe; Evelyn J Walsh; Timothy J Foster; Rachel M McLoughlin (PLoS Pathogens)
Staphylococcus aureus asymptomatically colonises the anterior nares, but the host and bacterial factors that facilitate colonisation remain incompletely understood. The S. aureus surface protein ClfB has been shown to mediate adherence to squamous epithelial cells in vitro and to promote nasal colonisation in both mice and humans. Here, we demonstrate that the squamous epithelial cell envelope protein loricrin represents the major target ligand for ClfB during S. aureus nasal colonisation. In vitro adherence assays indicated that bacteria expressing ClfB bound loricrin most likely by the "dock, lock and latch" mechanism. Using surface plasmon resonance we showed that ClfB bound cytokeratin 10 (K10), a structural protein of squamous epithelial cells, and loricrin with similar affinities that were in the low µM range. Loricrin is composed of three separate regions comprising GS-rich omega loops. Each loop was expressed separately and found to bind ClfB, However region 2 bound with highest affinity. To investigate if the specific interaction between ClfB and loricrin was sufficient to facilitate S. aureus nasal colonisation, we compared the ability of ClfB⁺S. aureus to colonise the nares of wild-type and loricrin-deficient (Lor⁻/⁻) mice. In the absence of loricrin, S. aureus nasal colonisation was significantly impaired. Furthermore a ClfB⁻ mutant colonised wild-type mice less efficiently than the parental ClfB⁺ strain whereas a similar lower level of colonisation was observed with both the parental strain and the ClfB⁻ mutant in the Lor⁻/⁻ mice. The ability of ClfB to support nasal colonisation by binding loricrin in vivo was confirmed by the ability of Lactococcus lactis expressing ClfB to be retained in the nares of WT mice but not in the Lor⁻/⁻ mice. By combining in vitro biochemical analysis with animal model studies we have identified the squamous epithelial cell envelope protein loricrin as the target ligand for ClfB during nasal colonisation by S. aureus.